2015
DOI: 10.1186/s12889-015-1611-y
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of modern contraceptive use during the postpartum period among women in Uganda: a population-based cross sectional study

Abstract: BackgroundThe rationale for promotion of family planning (FP) to delay conception after a recent birth is a best practice that can lead to optimal maternal and child health outcomes. Uptake of postpartum family planning (PPFP) remains low in sub-Saharan Africa. However, little is known about how pregnant women arrive at their decisions to adopt PPFP.MethodsWe used 3298 women of reproductive ages 15–49 from the 2011 UDHS dataset, who had a birth in the 5 years preceding the survey. We then applied both descript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

45
115
17
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(178 citation statements)
references
References 37 publications
45
115
17
1
Order By: Relevance
“…In our study, the longer time-to-contraceptive use observed among women who attended 1-3 ANC visits compared with those who attended the recommended four or more visits supports this finding as noted elsewhere [51]. Thus, strengthening the integration of family planning into ANC services [23,26,52,53] would certainly go a long way in promoting modern contraceptive use, particularly during the postpartum period.…”
Section: Discussionsupporting
confidence: 83%
“…In our study, the longer time-to-contraceptive use observed among women who attended 1-3 ANC visits compared with those who attended the recommended four or more visits supports this finding as noted elsewhere [51]. Thus, strengthening the integration of family planning into ANC services [23,26,52,53] would certainly go a long way in promoting modern contraceptive use, particularly during the postpartum period.…”
Section: Discussionsupporting
confidence: 83%
“…Conversely, mothers may become polarised by their beliefs that hormonal contraception has a negative impact on breastfeeding 20. In addition, as found by Rutaremwa et al ,21 desire for another child was significantly associated with not using contraception during the extended postpartum period, which is possibly due to lack of knowledge about safe birth spacing.…”
Section: Discussionmentioning
confidence: 95%
“…Several factors, methods and programs are already known including but not limited to ideas such as behavioural change motivation 21,59 , getting closer to the people 60 , and family education 61 . Other issues of barriers, generational change and provider behaviour have also been identified 62,63 . Yet, there is still the problem of unmet needs, which seems to be confounded by the mix-up of sexual behaviour vs sexual health.…”
Section: Implication For Further Studiesmentioning
confidence: 99%